Perdamaian Negatif dalam Kegagalan Resolusi Dewan Keamanan PBB dalam Konflik Suriah 2011-2019 - Shary Charlotte Henriette Pattipeilhy (Universitas Airlangga, 2021)
Since the first shot fired over a decade ago, there has been no comprehensivesolution to the Syrian Conflict. Despite countless efforts and interventionscarried out by the international community, perpetual peace still seems to be adistant dream. This includes resolutions and initiatives passed by the UnitedNations Security Council (UNSC). This article would explain further on whythese actions has minimum impact, therefore failed to attain stability in Syria.Utilizing the principle of Peace By Peaceful Means by Johan Galtung, along withconcepts related to International Conflict Resolutions, the results find that theUNSC has given the wrong diagnosis, prognosis, and treatment to the SyrianConflict. This is reflected within narratives found in resolutions passed by theUNSC that are laden with nuance of negative peace. A lot of stress has been putupon ‘resolving’ the Syrian Conflict to bring peace. Meanwhile, conflict is not anegation of peace. The author thus suggest that stability in Syria is more likelyto be attainable if resolutions reflect more upon the positive peace paradigm; bymeans of ‘managing’ and ‘transforming’ the Syrian conflict to restore the peace.